Příklady z matematiky

                   (x+5)(y-2) = (x+2)(y-1)

                   (x-4)(y+7) = (x-3)(y+4)

             xy -2x +5y -10=xy –x +2y -2

              xy  +7x-4y-28=xy +4x -3y -12

                       - x + 3y = 8  / ( 3)

                          3x – y = 16

                        -3x +9y = 24

                           3x – y = 16

                                 8y = 40

                                    y = 5

 

x =                   = 7

 

 

L1 = (7+5)(5-2) =12.3 = 36

P1 = (7+2)(5-1) = 9.4 = 36

 

 

L2 = (7-4)(5+7) = 3.12 = 36

P2 = (7-3)(5+4) = 4.9 = 36

 

 

 

                                 P = [ 7;  5 ]